Liver sinusoidal endothelial cells orchestrate NK cell recruitment and activation in acute inflammatory liver injury - Papaioannou, Sophia; See, Jia-Xiang; Jeong, Mingeum; Torre, Carolina de la; Ast, Volker; Reiners-Koch, Philipp-Sebastian; Sati, Ankita; Mogler, Carolin; Platten, Michael; Cerwenka, Adelheid; Stojanovic, Ana (Cell reports, 2023)
Liver sinusoidal endothelial cells (LSECs) rapidly clear lipopolysaccharide (LPS) from the bloodstream and establish intimate contact with immune cells. However, their role in regulating liver inflammation remains poorly understood. We show that LSECs modify their chemokine expression profile driven by LPS or interferon-γ (IFN-γ), resulting in the production of the myeloid- or lymphoid-attracting chemokines CCL2 and CXCL10, respectively, which accumulate in the serum of LPS-challenged animals. Natural killer (NK) cell exposure to LSECs in vitro primes NK cells for higher production of IFN-γ in response to interleukin-12 (IL-12) and IL-18. In livers of LPS-injected mice, NK cells are the major producers of this cytokine. In turn, LSECs require exposure to IFN-γ for CXCL10 expression, and endothelial-specific Cxcl10 gene deletion curtails NK cell accumulation in the inflamed livers. Thus, LSECs respond to both LPS and immune-derived signals and fuel a positive feedback loop of immune cell attraction and activation in the inflamed liver tissue.